Meta-Analysis: Effect of Acupuncture Therapy on HbA1c Levels in Type II Diabetes Mellitus - Wahyu, Fatimah; Prasetya, Hanung; Murti, Bhisma (Indonesian Journal of Medicine, 2024)
Background: Diabetes mellitus is a chronic condition that occurs when there is an increase in glucose levels in a person's blood because the body cannot produce enough of the insulin hormone, or cannot use the insulin it produces effectively. This study aims to estimate the effect of acupuncture therapy on changes in HbA1c in people with type II diabetes mellitus. Subjects and Method: This research is a systematic review and meta-analysis carried out using the PRISMA flow diagram and PICO model including Population = Type II diabetes patients; Intervention = Acupuncture Therapy; Comparison= No acupuncture therapy or sham acupuncture; Outcome= Change in HbA1c and quality of life. Article searches through journal databases include: PubMed, Science Direct, Google Scholar, Springer Link, BMC and Hindawi. Search keywords: acupuncture, AND "type 2 diabetes mellitus", "acupuncture for diabetes mellitus type 2" AND HbA1c OR "quality of life" AND "randomized controlled trial". Inclusion criteria are full paper articles, Randomized Controlled Trial (RCT) research. The measure of relationship used is Mean SD. Eligible articles were analyzed using the Revman 5.3 application. Results: Randomized Controlled Trial (RCT) from China, England, Iran, Egypt and Taiwan. Acupuncture therapy can reduce HbA1c in type II diabetes mellitus patients by 0.57 units higher than in controls (SMD -0.57; 95% CI= -1.15 to 0.02; p=0.060). Acupuncture therapy improved the quality of life in type II diabetes mellitus patients by 0.87 units compared to controls (SMD 0.87; 95% CI= 0.00 to 1.74; p=0.050). Conclusion: Acupuncture therapy is effective in reducing HbA1c levels and improving quality of life in patients with type II diabetes mellitus.